Résilience du pastoralisme sahélien : discours d’évidence institutionnels et journalistiques - Nadège Soubiale; Étienne Damome (Communiquer)
Since 2010, UN discourses have used the lexicon of resilience to define the axes of their development aid policy for the poor and vulnerable, and particularly the communities of Sahelian nomadic pastoralists. In a previous article, we showed through a lexicometric analysis how the French-speaking African press has been relaying, since 2014, these institutional discourses of pastoral resilience. In this article, a semio-discursive analysis of our corpus of press articles allows us to show that the UN and journalistic discourses on pastoral resilience are linked to obvious speeches of neoliberal orientations.